The impacts of climate change on peasant’s crop production in major crop producing zones in Ethiopia - Abrha Megos Meressa; Lewoye Bantie (Discover Sustainability)
Abstract This study aims to investigate the repercussions of climate change on crop production, focusing on cereals, pulses, oilseeds, and vegetables, and explore factors that influence crop productions in major agricultural producing zones in Ethiopia. Employing the One-step system GMM and Two-step system GMM methodologies, the study analyzes production dynamics from 2003/04 to 2021/22 within 21 selected zones spanning the Amhara, Oromia, Benishangul Gumuz, SNNP, and Sidama regions. Key factors influencing cereal production, including lagged production, the number of private peasant holders, land area, fertilizer application, precipitation, maximum average temperature, relative humidity, and regional factors are identified. Notably, precipitation emerges as a critical determinant affecting cereals, pulses, and oilseeds negatively. The study underscores the imperative for diversifying crops and reducing dependence on rain-fed agriculture. It proposes leveraging erratic rainfall patterns by constructing small-sized irrigation dams to capitalize on excess water during heavy rainfall seasons. Moreover, the adoption of temperature-resistant crop varieties and collaborative efforts with local administrations at various administrative levels are recommended to expand irrigated land, thereby bolstering resilience against climate variability and safeguarding rain-fed agriculture.